The boogeyman [videorecording (DVD)] - Beck, Scott, 1984-; Woods, Bryan, 1984-; Heyman, Mark, 1979-; Thatcher, Sophie; Messina, Chris; Blair, Vivien Lyra; Dastmalchian, David; Ireland, Marin; Hu, Madison; Nichols, Maddie; King, Stephen (20th Century Studios, 2023)
Still reeling from the heartbreaking death of their mother, a teenage girl and her younger sister find themselves hounded by a sadistic presence in their house and struggle to get their grieving father to pay attention before it's too late.